La práctica docente en los procesos de acreditación institucional para la calidad educativa (2017)
A learning strategy is the way in which the subject (student) approaches an object of study, interacts with him and gives meaning (Valero and Cortés, 2003:19), the teaching practice in the processes of accreditation is without place to doubt, the activity that more efforts Demand of the educator, and without which, even the most laudable of the pedagogical efforts would be but of a waste of goodwill but without the guarantee of justifying the learning of the educating. The purpose of this study is to understand the relationship between pedagogical practice and institutional accreditation processes for educational quality, with the help of participatory observation techniques, the implementation of personal interviews With each teacher and the collaboration of some of his students, who through interview will let us know their perceptions about the teaching exercise of each teacher and how they believe that this is related to the processes of quality. In conclusion it can be understood that the level of academic education and more exactly the pedagogical practice of the teacher, has a determinant and significant relationship in the processes of institutional accreditation; since the higher the level of teacher training allows to provide greater response and technical support to the required curricular processes.